Experiences of stigma and HIV care engagement in the context of Treat All in Rwanda: a qualitative study - Ingabire, Charles; Watnick, Dana; Gasana, Josephine; Umwiza, Francine; Munyaneza, Athanase; Kubwimana, Gallican; Murenzi, Gad; Anastos, Kathryn; Adedimeji, Adebola; Ross, Jonathan (BMC public health, 2023)
'Treat All' policies recommending immediate antiretroviral therapy (ART) soon after HIV diagnosis for all people living with HIV (PLHIV) are now ubiquitous in sub-Saharan Africa. While early ART initiation and retention is effective at curtailing disease progression and transmission, evidence suggests that stigma may act as a barrier to engagement in care. This study sought to understand the relationships between HIV stigma and engagement in care for PLHIV in Rwanda in the context of Treat All. Between September 2018 and March 2019, we conducted semi-structured, qualitative interviews with adult PLHIV receiving care at two health centers in Kigali, Rwanda. We used a grounded theory approach to data analysis to develop conceptual framework describing how stigma influences HIV care engagement in the context of early Treat All policy implementation in Rwanda. Among 37 participants, 27 (73%) were women and the median age was 31 years. Participants described how care engagement under Treat All, including taking medications and attending appointments, increased their visibility as PLHIV. This served to normalize HIV and use of ART but also led to high levels of anticipated stigma in the health center and community at early stages of treatment. Enacted stigma from family and community members and resultant internalized stigma acted as additional barriers to care engagement. Nonetheless, participants described how psychosocial support from care providers and family members helped them cope with stigma and promoted continued engagement in care. Treat All policy in Rwanda has heightened the visibility of HIV at the individual and social levels, which has influenced HIV stigma, normalization, psychosocial support and care engagement in complex ways. Leveraging the individual and community support described by PLHIV to deliver evidence-based, peer or provider-delivered stigma reduction interventions may aid in attaining Treat All goals.